The Impact Of The Trans Java Toll Road On Industry Micro Small Food And Beverage Sector - Riki Hurip Djumantara; I Dewa Gede Karma Wisana (Oikonomia : Journal of Management Economics and Accounting, 2025)
This study aims to evaluate the impact of the Trans Java Toll Road on the growth of small and micro enterprises (SMEs) in the food and beverage sector using the fixed-effect difference-in-difference method. The data used are sourced from the Village Potential Statistics (PODES) for the years 2008–2020, covering 70 districts/cities that are either traversed or not traversed by the Trans Java Toll Road. The findings reveal that, during the initial phase of operation, the toll road had a negative and statistically significant impact on the number of SMEs in the food and beverage sector. However, after operating for two periods, or approximately six years, the impact shifted to being positive and significant. This indicates that while the infrastructure initially posed challenges or disruptions to small-scale industries, in the long term, the Trans Java Toll Road serves as a stimulus for better growth in the sector. These findings are important for policymakers, as they highlight the need to not only focus on the long-term benefits of infrastructure development but also to design mitigation strategies to address potential short-term negative impacts, especially on small and micro businesses that are more vulnerable to economic shifts caused by large-scale infrastructure projects.